Omnichannel Integration and Positive Word of Mouth among Customers in Sri Lanka's Supermarket Sector: The Mediating Role of Flow Experience - W. K. C. S. Walpola; D. M. P. Sewwandi; R. H. Banduge, (Journal of Sales, Service and Marketing Research (e-ISSN: 2582-7804), 2025)
The research investigates the influence of Omni channel integration on Positive Word of Mouth (PWOM) among supermarket customers in Colombo, Sri Lanka with a particular focus on focus on flow experience, which is the mediator. Omnichannel integration has cropped up as one of the essential strategies in providing seamless and engaging customer experiences both offline and online, which includes informational, transactional, and relational integrations. PWOM represents a pivotal aspect of consumer behavior, significantly contributing to brand advocacy, customer retention, and market expansion. However, how omnichannel integration drives PWOM even through the action of psychological mediators such as flow experience, a state of deep immersion, and engagement is not well understood and recognized. In this context, the research examines both the direct and indirect effects of omnichannel integration on PWOM within supermarket industry in Sri Lanka. In the quantitative cross sectional research design, data was gathered from 350 supermarket customers via an online questionnaire. All types of omnichannel integration had a significant effect on PWOM based on statistical analyses, and mediation analysis using PROCESS macro in SPSS. Whereas the effects of informational and transactional integrations were strong and direct, relational integration had an indirect and mostly mediated effect via flow experience. These findings thus underline the power of flow experience in enhancing engagement and satisfaction for consumers, and more strongly advocate than before for increased omnichannel integration effects toward PWOM. From a theoretical perspective, this paper highlights the role of flow experience as a key mediator in explaining the link between omnichannel integration and PWOM. By situating the research in an developing market, respective study emphasizes how contextual aspects shape the effectiveness of omnichannel strategies. In a practical perspective, the findings emphasize the importance of integrating informational, transactional, and relational elements across channels to deliver personalized and immersive experiences. The study suggests that strategies, that encourage flow experience, including integrated payment systems, personalization of promotions, and seamless interactions to enhance customer satisfaction, loyalty, and advocacy.